Interaction of octaethylene glycol n-dodecyl monoether with dioctadecyldimethylammonium bromide and chloride vesicles - Barreleiro, PCA; Olofsson, G.; Brown, W.; Edwards, K.; Bonassi, N. M.; Feitosa, E. (Amer Chemical Soc, 2002)
Several different methods were used to investigate the vesicle-to-micelle transition induced by the addition of the nonionic surfactant octaethylene glycol n-dodecyl monoether (C12E8) to spontaneously formed vesicle dispersions of dioctadecyldimethylammonium bromide and chloride (DODAX, X = Cl- and Br-). Dynamic light scattering reveals that fast mode micelles are formed upon addition of C12E6. The micellar mode becomes progressively dominant as the C12E8/DODAX molar ratio (R) is increased until the vesicle-to-micelle transition is complete. Turbidity, calorimetry, fluorescence quantum yield, and anisotropy measurements indicate two critical compositions: the first, R-sat, when the vesicle bilayer is saturated with C12E8 and the second, R-sol, which corresponds to the complete vesicle-to-micelle transition. Below R-sat the vesicles swell due to incorporation of the surfactant into the vesicle bilayer, and above R-sat mixed micelles and bilayer structures coexist, the determined R-sat and R-sol range from 0 to 1 and 4 to 6, respectively, depending on the surfactant counterion and the experimental method used. Cryo-transmission electron microscopy micrographs show that when R approximate to 4, micelles coexist with extended bilayer fragments. In pure DODAX (1.0 mM) dispersions, unilamellar vesicles are observed. According to the DSC results, C12E8 lowers the gel-to-liquid crystalline transition temperature, T-m, of DODAX and broadens the main transition peak which disappears around R approximate to 5 and 6 for DODAC and DODAB, respectively.